Diagnostic Capacity of Central Hemodynamic Monitoring at Thoracic Cancer Surgery - A. M. Batyrshina; M. S. Vetsheva (Общая реаниматология)
Objective: to study hemodynamic changes and the development rate of adaptive reactions in patients with hypokinetic circulation during lung resections varying in volumes. Subjects and methods. Thirty-eight patients with hypo-kinetic circulation, who had undergone sublobar resections, lobectomies, and pneumonectomies, were examined. The values of hemodynamics and gas exchange were recorded at the basic surgical stages and in the early postoperative period (on days 1, 3, 7, and 10). Results. When the patient is placed in the lateral position, the lung is switched off, or the surgical pneumothorax is less than 10—12%, cardiac index changes generally fail to give rise to the decompensation of adaptive processes in the cardiovascular system if the volume of a surgical intervention does not exceed that of sublobar resections or lobectomies. A 15% or more change in cardiac index during controlled lung collapse even with the minimum volume of surgery is indicative of the breakdown of physiological adaptation processes and may manifest itself through the symptoms of cardiorespiratory decompensation in both intra- and postoperative periods. Conclusion. The patients with baseline poor, hypokinetic circulation need not only adequate preoperative estimation of central hemodynamic values, but also continuous intraoperative monitoring of the basic parameters of central hemodynamics. The magnitude of a reduction in cardiac index is prognostically important at the stage of one-lung ventilation during surgical pneumothorax. Key words: hypokinetic circulation, thoracic cancer surgery, central hemodynamic monitoring.